Hair and Wool as Indicators of Environmental Pollution by Man-Made and Geochemical Sources - Fatima Sharipovna Nazarova; Nargiza Eshmamatovna Dzhumanova (Researchparks Publishing, 2022)
The concentration of trace elements in the human body is regulated very finely. This control is carried out by certain proteins, hormones and depositing systems (bone tissue, hair, cornea, etc.). On the other hand, the relationship between metal ions and their binding substances is so close that changes in the state of the body can be the result of both increased and decreased content of metal ions compared to the norm. The study of tissues and body fluids for the content of elements is therefore a very important diagnostic test. A human body weighing 70 kg contains 1050 g Ca , 245 g K, 105 g N a, 35 g M g , 700 g P, 100 g C l , 3 g Fe , 20 mg M n . Some of the elements such as Cs , Rb , Sr , Ni are relatively non-toxic. Others are highly toxic - Sb , As , Ba , Rb , Hg , Ag , etc. The toxicity is strongly influenced by the form in which the metal ion is located. The formation of fat- soluble complexes with organic ligands increases toxicity. A classic example is Minimat 's disease , the cause is the transformation of inorganic mercury from wastewater into methylmercury under the action of vitamin B12 contained in microorganisms, which then enters the body with water or food.